Ordenamento territorial na perspectiva da governança em Unidade de Conservação no litoral sul de Alagoas - França, Eduina Bezerra (2019)
The coast is an integrated space formed by different environmental systems and by dynamic territorial systems with diversified characteristics that includes a mosaic of ecosystems. Given the fragility, intrinsic of complex environments such as coastal areas, there is an increasing interest in strategic conservation actions. Conservation units are protected areas by law, and in Brazil they are divided into two main groups: integral protection and sustainable use. The Environmental Protection Areas (APAs) make up the sustainable use group and aim at spatial planning in a way that guarantees the use of natural resources, and the conservation and maintenance of their ecosystems. In Brazil, the management of conservation units is still little discussed in the sense of governance and at the same time it directs the approaches to the application of territorial planning methodologies and policies that will mitigate conflicts and effect more democratic and participatory practices. The present research is about an Environmental Protection Area (APA). The aim is to understand territorial planning in an integrated way between the physical and social elements within a systemic vision. Thus, the general objective is to analyze the territorial planning in the perspective of governance in the Environmental Protection Area of Piaçabuçu, litoral Sul of Alagoas. The methodology consists of: bibliographical survey, theoretical and methodological basis, documentary survey in public bodies of historical and legal character, basic mapping, field visit, interview with managers, traditional communities, fishermen's colony and representative of the municipal agency. The UC governance analysis was carried out under the view of the decalogue proposed by the Spanish geographer Barragán Muñoz (2014a), who seeks to assess geographic environments and systematize a model of effective governance in coastal zones. Studying coastal conservation unit in the governance prospect is a challenge, since it refers to a unique, conflictive and integrated system.________________________________________________________________________________________________________________________________